The Psychological Factors Influencing the EFL University Students' Development of Grammar Knowledge within the Online Discussion Atmospheres - AbdulGhafoor, Najla Hais; Challob, Ala'a Ismael (Al-Adab Journal, 2022)
Within the online learning atmospheres, language learners may confront certain obstacles in learning English grammar. Those obstacles may be associated to psychological factors which represent influential barriers on developing the grammatical knowledge of the EFL learners at the university level. Thus, the aim of the current research is to find out the exact psychological factors that influence the students' grammar knowledge. To achieve that aim, a close-ended questionnaire was designed to investigate the students' responses toward the psychological factors that can influence their grammatical knowledge. The sample of the research was the Iraqi EFL university students at the second year of the academic year (2020/2021) in English Department at the University of Anbar. At the first course, the sample of the participants (n=33) was exposed to online discussion learning activities for thirteen weeks to learn English grammar. At the end of the course, they were asked to respond to the items of the questionnaire. Depending on: T-test formula for one sample; weighted mean and percentage weight of the tenth items of the psychological domain, the collected data were analyzed. Results showed that the priority of some psychological factors like: anxiety, aptitude, attitude, and motivation were prominent and affective within the online discussion environments.Accordingly, these factors are necessary to be explored and governed within the language learning process in general and online learning in particular to get better students' performance.